Identification of the OsCML4 Gene in Rice Related to Salt Stress Using QTL Analysis - Saleem Asif; Eun-Gyeong Kim; Yoon-Hee Jang; Rahmatullah Jan; Nari Kim; Sajjad Asaf; Lubna; Muhammad Farooq; Kyung-Min Kim (Plants, 2022)
Soil salinity is a major abiotic stress that causes disastrous losses in crop yields. To identify favorable alleles that enhance the salinity resistance of rice (Oryza sativa L.) crops, a set of 120 Cheongcheong Nagdong double haploid (CNDH) lines derived from a cross between the Indica variety Cheongcheong and the Japonica variety Nagdong were used. A total of 23 QTLs for 8 different traits related to salinity resistance on chromosomes 1–3 and 5–12 were identified at the seedling stage. A QTL related to the salt injury score (SIS), qSIS-3b, had an LOD score of six within the interval RM3525–RM15904 on chromosome 3, and a phenotypic variation of 31% was further examined for the candidate genes. Among all the CNDH populations, five resistant lines (CNDH 27, CNDH 34-1, CNDH 64, CNDH 78, and CNDH 112), five susceptible lines (CNDH 52-1, CNDH 67, CNDH 69, CNDH 109, and CNDH 110), and the parent lines Cheongcheong and Nagdong were selected for relative gene expression analysis. Among all the genes, two candidate genes were highly upregulated in resistant lines, including the auxin-responsive protein IAA13 (Os03g0742900) and the calmodulin-like protein 4 (Os03g0743500-1). The calmodulin-like protein 4 (Os03g0743500-1) showed a higher expression in all the resistant lines than in the susceptible lines and a high similarity with other species in sequence alignment and phylogenetic tree, and it also showed a protein–protein interaction with other important proteins. The genes identified in our study will provide new genetic resources for improving salt resistance in rice using molecular breeding strategies in the future.